Reducing frailty in frail people with multiple sclerosis: Feasibility of a 6-week multimodal exercise training program - Tobia Zanotto; Abbas Tabatabaei; Sharon G. Lynch; Jianghua He; Madison Lysaught; Pedram Ahmadnezhad; Jane Ibude; Hannes Devos; Lee D. Chaves; Bruce R. Troen; Jacob J. Sosnoff (PLoS ONE, 2026)
Background Frailty is increasingly recognized as a prevalent and debilitating condition in people with multiple sclerosis (MS) and is linked to poorer health outcomes. However, targeted interventions remain limited. The objective of this study was to examine the feasibility of a multimodal exercise training (MET) program to reduce frailty in frail people with MS. Materials and methods Sixteen frail people with MS (age = 55.0 ± 7.7 years, 81.3% female, Fried frailty score ≥3) participated in this pilot randomized controlled trial. Participants were randomly assigned to a 6-week MET program consisting of virtual reality treadmill training + resistance training (n = 8) or to a waitlist control group (n = 8). Feasibility outcomes included recruitment, retention, and adherence rates as well as safety and user engagement throughout the study (Study Participant Feedback Questionnaire—SPFQ). Exploratory outcomes were collected at baseline and 6 weeks and included the Evaluative Frailty Index for Physical Activity (EFIP), the 54-item MS Quality of Life questionnaire (MSQoL-54), the Modified Fatigue Impact Scale (MFIS), and the Physiological Profile Assessment (PPA). Results Fourteen participants, eight in the intervention group and six in the control group, completed the study. The recruitment rate was 0.33 participants/week, retention was 87.5%, and adherence was high, with participants completing 97.2% of planned training sessions. No adverse events or training-related pain were recorded. The data collection procedures were successfully implemented with complete outcome data. Participants agreed or strongly agreed with 95.7% of applicable SPFQ items, indicating high levels of engagement and satisfaction with the trial. Between-group differences in baseline to 6-week change were: EFIP −0.07 (95% CI: −0.14, −0.00); MSQoL-54 mental health +21.24 (95% CI: 7.32, 35.16); MSQoL-54 physical health +19.26 (95% CI: 5.61, 32.91); MFIS −11.46 (95% CI: −18.34, −5.13); and PPA −0.09 (95% CI: −1.19, 1.01). Conclusion The MET program was safe, feasible, and well-received by frail people with MS. These findings support the viability of MET for future larger-scale trials targeting frailty reduction in this population. Trial registration ClinicalTrials.gov NCT06042244